Expressão e perfil mutacional do gene BCR-ABL em pacientes com leucemia mieloide crônica tratados com inibidores de tirosina quinase - Almeida Filho, Tarcísio Paulo de (2017)
Most patients with chronic myeloid leukemia (CML) express the transcripts b2a2, b3a2 or both of the BCR-ABL gene. The role of these transcripts in the prognosis of patients undergoing treatment with tyrosine kinase inhibitors (ITKs) has been poorly investigated and remains unclear to date. In this study, we evaluated the prognostic value of the main transcripts in patients with CML, by evaluating the expression and mutational profile of the BCR-ABL gene in patients treated with ITKs. Sixty patients with CML were evaluated transversally. Demographic, hematological, and clinical data and mutation profile of CML patients treated with ITKs were obtained from medical records. Molecular analyzes for the determination of transcripts and mutations (T315, E255V and Y253H) were performed by the qPCR technique. Statistical analyzes were performed using the Kruskal-Wallis or one-way ANOVA tests, depending on the normality of the data. The level of significance was 0.05 and p values of less than 0.05 were considered significant. Of the sixty patients, 12 (20%) expressed the b2a2 transcript, 18 (30%) the b3a2 transcript, 10 (16.7%) both b2a2/b3a2 transcripts and 20 (33.3%) had undetectable levels. Twenty-eight patients (46.7%) were female and 32 (53.3%) were males, with a mean age of 46.5 ± 15.7 years (ranging from 19-82). The comparative analysis of hematological data with transcripts showed a significant difference in the number of leukocytes in patients expressing the b2a2 and b3a2 transcripts (p <0.05), with patients with the b2a2 transcript associated with lower amounts. The other data, hematological and clinical, did not show statistically significant differences in relation to transcripts (p>0.05). Regarding mutations of the kinase domain, the presence of the T315, E255V and Y253H mutations in the study patients was not evidenced. These are the first results found in this population, being necessary more studies with a greater number of individuals and evaluation of the cytogenetic and molecular responses to the treatment. If confirmed as a prognostic factor capable of providing better outcomes and response to treatment, the transcripts could be used in the elaboration of new mathematical models for patient risk stratification and in the selection of the best therapy with ITKs for patients with CML.